Impact Analysis of Inflation, ROA, FDR, and Financing on Non-Performing Financing in Indonesian Islamic Banks - Yulia, Yulia; Helvira, Reni; Tunisa, Jakiyah (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2024)
This study aims to analyze the influence of Inflation, ROA, FDR, and financing on the NPF in Indonesia Islamic Banks. The research employs a quantitative approach and an associative research design. Secondary data is utilized for the study, with a monthly time series spanning the period 2011-2021. The analysis is conducted using OLS analysis with the R Studio 4.1.3 software.The results of this study indicate that, in partial terms: 1) The inflation variable has a significant positive impact on NPF individually; 2) The ROA variable has a significant negative impact on NPF individually; 3) The FDR variable has a non-significant positive impact on NPF individually; 4) The total financing variable has a significant negative impact on NPF individually; 5) Simultaneously, there is a significant influence of Inflation, ROA, FDR, and Total Financing on NPF. There was no growth in NPF in Indonesian Islamic Banks following the Covid-19 epidemic. On the contrary, NPF decreased compared to the previous year, which was 2019. This was attributed to Islamic banks extending financing to the real sector. Additionally, the government issued policies related to financing restructuring through the Financial Services Authority Regulation No. 11/POJK.03/2020 concerning National Economic Stimulus as a Countercyclical Policy.